PEMBERDAYAAN KADER POSYANDU DALAM PEMANTAUAN TUMBUH KEMBANG BALITA MENGGUNAKAN KPSP DAN APLIKASI “PRIMAKU” SEBAGAI DETEKSI DINI STUNTING DI DESA TANAH MERAH KABUPATEN KAMPAR - YANTI,; LAILIYANA,; FINDY HINDRATNI, (KRIDA CENDEKIA, 2022)
This community service activity is one of the efforts to realize the Tri Dharma of higher education. The activity was carried out from February to September 2022, which was located in Tanah Merah Village, Siak Hulu District, Kampar Regency. The target of community service is the Tanah Merah Village Integrated Healthcare Center, totaling 30 participants from 10 Integrated Healthcare Center located in the working area of the Siak Hulu Health Center. The form of community service is in the form of training for cadres, this activity is expected to increase the knowledge and ability of cadres in monitoring the growth and development of infants under five using Development Pre-Screening Questionnaire and the "Primaku" application. Implementation of training activities in the form of material debriefing, demonstration of how to assess growth and development of infants under five, practice of assessing growth and development in Integrated Healthcare Center and evaluation of implementation in the field. The training venue in the village office hall and practice activities for assessing growth and development were held at the Integrated Healthcare Center Kenanga, Cahaya Bunda and Smiles Toddler. The expected result is the achievement of increased knowledge and ability of cadres in monitoring the growth and development of infants under five using Development Pre-Screening Questionnaire and the "Primaku" application. From the evaluation conducted through the pre-post test and observation of cadre counseling, it was found that the results of increasing the knowledge and ability of cadres in analyzing the results of monitoring the growth and development of infants under five. Cadres have been able to apply assessments of toddler development using Development Pre-Screening Questionnaire and have tried to socialize the “Primaku” application to parents when they come to the Integrated Healthcare Center. the Integrated Healthcare Center are at the forefront of detecting early growth and development of infants under five in the community by providing optimal services.